Simulation of slope soil erosion intensity with different vegetation patterns based on cellular automata model - Sheng, Yan; Zhang, Shangxuan; Li, Long; Cao, Zhiming; Zhang, Yu (Frontiers in Environmental Science, 2025)
IntroductionSoil erosion plays a crucial role in soil and water conservation management, as well as in ecological construction planning. This study focuses on the slopes of three planting patterns (uniform distribution, aggregation distribution, and random distribution), along with bare slopes, in the Baojiagou watershed of the Pisha Sandstone area, based on soil erosion intensity grade maps after rainfall from 2021 to 2023.MethodsA method combining Multi-Criteria Evaluation (MCE) and the CA-Markov model is used to analyze the spatial variation of soil erosion intensity types on different slopes. This approach integrates multiple influencing factors and generates a suitability map for the conversion of soil erosion intensity types. Ultimately, the dynamic characteristics of soil erosion in 2023 are simulated under various slope conditions.ResultsResults indicated: (1) The spatial distribution of simulated soil erosion intensity grade maps for different slopes largely aligned with actual maps, and regions with soil erosion depth greater than 3 cm were resistant to transitioning to lower erosion zones. (2) The Kappa coefficients for simulated soil erosion intensity in uniform distribution, random distribution, aggregate distribution, and bare control slopes were 65.24%, 73.62%, 75.88%, and 69.06%, respectively, confirming the feasibility of the CA-Markov model for simulating soil erosion dynamics. (3) The simulation of soil erosion intensity on different slopes in 2023 revealed that erosion intensity on uniformly distributed, aggregated, and bare control slopes remained predominantly in the erosion zone with a depth of 1–2 cm, while randomly distributed slopes experienced a shift from mild erosion area to slight erosion area.DiscussionThis study improves the understanding of soil erosion across different vegetation patterns and demonstrates the applicability of the CA-Markov model for simulating dynamic erosion on slopes. The findings contribute to the development of broader ecological models and offer insights into vegetation management and erosion control strategies for similar landscapes.